E-Learning: An Implication of Covid-19 Pandemic for the Teaching and Learning of Arabic and Islamic Studies in Ogun State’s Tertiary Institutions - Abdul-Ganiy Kayode Ahmad (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2022)
The covid-19 pandemic has significantly brought a lot of challenges and innovations to the educational sector. This study, therefore, examined the level of adoption of e-learning as an implication of the Covid-19 pandemic for teaching and learning of Arabic (ARA) and Islamic Studies (ISS) in Ogun State's tertiary institutions that offer either one or the two twin courses using descriptive survey research design. The population comprised all thirty-four (34) lecturers of the twin disciplines in the five (5) Ogun State’s tertiary institutions where the courses are offered. All the lecturers constituted the study sample using total enumeration sampling techniques. Findings from the study revealed relatively high knowledge of e-learning tools among the lecturers of ISS and ARA (A.W.M. = 2.91 > Criterion Mean of 2.50). However, this study also indicated that their levels of utilization were abysmally low (A.W.M. = 2.20 < Criterion Mean of 2.50). It was also found out that several challenges such as poor ICT knowledge of lecturers and students, lack of gadgets and poor network among others are barriers (A.W.M. = 3.06 > Criterion Mean of 2.50). This study concluded that to be more effective and efficient, Arabic and Islamic Study lecturers should further develop and improve their competency in using ICT resources for e-learning during and after the Covid-19 pandemic. It is recommended that Arabic and Islamic studies lecturers be proactive in acquiring sound functional digital knowledge to remain relevant in the profession.